2014
DOI: 10.1039/c4nr02345e
|View full text |Cite
|
Sign up to set email alerts
|

Direct chemical synthesis of L10-FePtAu nanoparticles with high coercivity

Abstract: We report a facile synthesis of hard magnetic L10-FePtAu nanoparticles by coreduction of Fe(acac)3, Pt(acac)2 (acac = acetylacetonate), and gold acetate in oleylamine. In the current reaction condition, NP sizes are controlled to be 5.5 to 11.0 nm by changing the amount of Au doping. When the Au composition in the NPs is higher than 14%, the hard magnetic NPs are directly obtained without any annealing. The highest coercivity of 12.15 kOe at room temperature could be achieved for the NPs with 32% Au doping, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 34 publications
2
43
1
Order By: Relevance
“…The coercivity of the sample synthesized with Ag was much higher than the reported values for chemically synthesized FePt nanocomposites [19][20][21][22]. This suggests that the increase in the coercivity was caused by the addition of Ag to the FePt nanocrystals and that the grain boundaries of the nonmagnetic Ag metal acted as pinning sites, disrupting magnetic coupling between individual FePt nanocrystallites and hindering domain wall motion at an external magnetic field.…”
Section: Journal Of Nanomaterialscontrasting
confidence: 38%
See 1 more Smart Citation
“…The coercivity of the sample synthesized with Ag was much higher than the reported values for chemically synthesized FePt nanocomposites [19][20][21][22]. This suggests that the increase in the coercivity was caused by the addition of Ag to the FePt nanocrystals and that the grain boundaries of the nonmagnetic Ag metal acted as pinning sites, disrupting magnetic coupling between individual FePt nanocrystallites and hindering domain wall motion at an external magnetic field.…”
Section: Journal Of Nanomaterialscontrasting
confidence: 38%
“…Fabrication of FePt nanostructures by chemical synthesis is a promising alternative, but achieving high coercivity with chemical synthesis methods has been difficult [19][20][21][22]. The problem has been attributed to the difficulty of controlling nanocomposite structures.…”
Section: Introductionmentioning
confidence: 99%
“…The small M s is not likely due to the dilution effect of the substituted elements. Such reduced M s was also observed in many CoPt and FePt nanoparticles . It is also reported the M s could be increased significantly in FePt by tuning the 3 d ‐5 d interaction via the minor addition of Au .…”
mentioning
confidence: 54%
“…Such reduced M s was also observed in many CoPt and FePt nanoparticles. [18][19][20] It is also reported the M s could be increased significantly in FePt by tuning the 3d-5d interaction via the minor addition of Au. [20] Thus the reduced M s should result from the partial delocalization of Co 3d electrons likely induced the strong interaction with B or Si.…”
mentioning
confidence: 99%
“…Most reports focus on the addition of a third element dopant keeping the stoichiometry between Fe and Pt fixed with the purpose of reducing ordering temperature. [17][18][19][20][21][22][23] To our knowledge only one other study considered the chemical synthesis of an Fe-Pt-Ni alloy, in which (FePt) 1-x Ni x nanoparticles were obtained. It was shown that the addition of Ni in an FePt phase suppresses the transformation from the disordered fcc to the ordered fct L1 0 phase, up to a certain Ni content, beyond which nanoparticles in the L1 2 phase are obtained.…”
Section: Introductionmentioning
confidence: 99%